EFEK HIDROTERAPI TERHADAP LANSIA DENGAN HIPERTENSI DI KLINIK PRATAMA RAWAT INAP GRAHA AMANAH - Mayasari, Destianti Indah; Pramithasari, Intan Diah; Rahmasari, Intan (Nursing Sciences Journal, 2024)
Hypertension is still a threat to increase blood pressure, especially in the elderly. Hypertension is "The Silent Killer" because hypertension sufferers do not feel the symptoms when their blood pressure increases and can attack the elderly. Many complementary therapies have been used to treat hypertension in the elderly, but in reality they still show less significant reductions in blood pressure. This condition shows that the treatment of hypertension in the elderly has not been completed. Therefore, hydrotherapy intervention is needed to reduce high blood pressure in the elderly. Water therapy is a method of body treatment that uses water as a healing agent. The aim of the research was to determine the effect of hydrotherapy on elderly people with hypertension at the Graha Amanah Inpatient Primary Clinic. Quasi experimental research design pre – post test with control group with hydrotherapy treatment. The research respondents were elderly people with hypertension at the Graha Amanah Inpatient Primary Clinic. The sampling technique used was purposive sampling. Research results: There is a significant effect between hydrotherapy and blood pressure in the elderly. It is hoped that this research will provide benefits for improving the quality of life of the elderly and increasing the implementation of complementary therapies in nursing interventions, especially for the elderly with hypertension so that they can maintain blood pressure within normal limits.